Advanced Fluid Mechanics and Heat Transfer for Engineers and Scientists - Schobeiri, Meinhard T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The current book, Advanced Fluid Mechanics and Heat Transfer is based on author's four decades of industrial and academic research in the area of thermofluid sciences including fluid mechanics, aero-thermodynamics, heat transfer and their applications to engineering systems. Fluid mechanics and heat transfer are inextricably intertwined and both are two integral parts of one physical discipline. No problem from fluid mechanics that requires the calculation of the temperature can be solved using the system of Navier-Stokes and continuity equations only. Conversely, no heat transfer problem can be solved using the energy equation only without using the Navier-Stokes and continuity equations. The fact that there is no book treating this physical discipline as a unified subject in a single book that considers the need of the engineering and physics community, motivated the author to write this book. It is primarily aimed at students of engineering, physics and those practicing professionals who perform aero-thermo-heat transfer design tasks in the industry and would like to deepen their knowledge in this area. The contents of this new book covers the material required in Fluid Mechanics and Heat Transfer Graduate Core Courses in the US universities. It also covers the major parts of the Ph.D-level elective courses Advanced Fluid Mechanics and Heat Transfer that the author has been teaching at Texas A&M University for the past three decades.
Introduction -- Vector and Tensor Analysis, Applications -- Kinematics of Fluid Motion -- Differential Balances in Fluid Mechanics -- Integral Balances in Fluid Mechanics -- Inviscid Potential Flows -- Viscous Laminar Flow -- Laminar-Turbulent Transition -- Turbulent Flow, Modeling -- Free Turbulent Flow -- Boundary Layer Aerodynamics -- Boundary Layer Heat Transfer -- Compressible Flow -- Flow Measurement Techniques, Calibration -- Heat Transfer.
Keywords: Fluid mechanics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Physics; Engineering mathematics; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Classical and Continuum Physics; Engineering Mathematics; Fluid mechanics; Heat -- Transmission